The local nexus network: Exploring the future of localised food systems and associated energy and water supply - Cottee, J; López-Avilés, A; Behzadian, K; Bradley, D; Butler, D; Downing, C; Farmani, R; Ingram, J; Leach, M; Pike, A; De Propris, L; Purvis, L; et al. (Springer International Publishing Switzerland, 2016)
The Local Nexus Network is addressing the intersection of two important emerging research areas, re-distributed manufacturing and the food-energy-water nexus. It is an on-going initiative which aims to develop an evidence-based comprehensive research agenda and foster an inclusive community of researchers and stakeholders for sustainable local food-energy-water nexuses. This paper presents the conceptual framing for understanding the challenges of local nexus, reports empirical findings around a particular case study, and makes initial reflections on the research and practical challenges and opportunities.